An overview of the Corpus Protagoreum: A Bibliographical Note on Laks and Most’s Early Greek Philosophy - Barrionuevo, Sergio Javier (Revista Archai, 2018)
An overview of the Corpus Protagoreum: A Bibliographical Note on Laks and Most’s Early Greek Philosophy